2019
DOI: 10.3390/vetsci7010004
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Mortality Caused by Aeromonas hydrophila in Wild-Caught Red-Eyed Crocodile Skinks (Tribolonotus gracilis)

Abstract: Aeromonas hydrophila, a Gram-negative bacterium commonly found in aquatic environments, is pathogenic to amphibians, reptiles, and mammals. In human medicine, the clinical symptoms of aeromonad infection include not only gastroenteritis but also extraintestinal infections, such as wounds, cellulitis, and septicemia, in immunocompromised and immunocompetent individuals. In this study, ten red-eyed crocodile skinks (Tribolonotus gracilis) that shared the same space were found dead 7 days after being shipped from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…In animals, Aeromonas infections are also common, and numerous virulence factors are also demonstrated in the isolates in these cases. Nevertheless, the symptoms of Aeromonas infection develop most often in the presence of other factors, e.g., stress associated with captivity, the transport of animals, or an inappropriate ambient temperature [58].…”
Section: Discussionmentioning
confidence: 99%
“…In animals, Aeromonas infections are also common, and numerous virulence factors are also demonstrated in the isolates in these cases. Nevertheless, the symptoms of Aeromonas infection develop most often in the presence of other factors, e.g., stress associated with captivity, the transport of animals, or an inappropriate ambient temperature [58].…”
Section: Discussionmentioning
confidence: 99%
“…MMCs aggregates contained approximately equal proportions of melanin and hemosiderin granules in the center of the portal tract in the hepatic parenchyma of freshwater turtles (Trachemys scripta) (Divers et al, 2010). Red-eyed crocodile skinks (Tribolonotus gracilis) appeared in two forms, large polymorphic MMCs aggregates and small diffused macrophages scattered all over the hepatic tissue (Kwon et al, 2019). Akiyoshi et al (2015) designed a study on the livers of 23 reptilian species and they revealed the distribution of MMCs in different zones in hepatic parenchyma.…”
Section: Total Mmcs Covered Area (%)mentioning
confidence: 99%
“…For example, some species of tick (Ixodidae and Argasidae) and mites (Macronyssidae, Trombiculidae) often feed on reptiles as well as on humans (Table 1). The macronyssid mite Ophionyssus natricis, one of the most widely distributed mite species of snakes, is a mechanical vector of Aeromonas hydrophila, the causative agent of hemorrhagic disease in reptiles as well as of gastroenteritis, and in rare cases, of necrotizing fasciitis in humans [20,21]. In the past decade, the epidemiological role of argasid and ixodid ticks as vectors of zoonotic pathogens has received great attention.…”
Section: Box 2 Reptiles As Food and Medicamentsmentioning
confidence: 99%